L. Munatius Plancus : Serving and Surviving in the Roman Revolution - Watkins, Thomas H. (Routledge Ancient Biographies Ser, 2018)
Cover -- Title -- Copyright -- Contents -- List of illustrations -- Acknowledgments -- 1 The evidence: discontinuity, biases, and hypotheses -- 2 Family and homeland: the Munatii Planci of southern Latium -- 3 Plancus the Caesarian, 54-44: from legate to consul designate -- 4 Plancus without Caesar: proconsul of Gaul, March-December 44 -- 5 Plancus the reluctant warrior: January-July 43 -- 6 Plancus the Antonian: late 43-mid 32 -- 7 Plancus in transition and Horace, Ode 1.7 -- 8 Plancus the Augustan: mid-32-22 -- Epilogue: Perilous prominence: the Tivoli villa, the Temple of Saturn, and the mausoleum through the centuries -- Appendix I L. Licinius Crassus and the Munatii Planci -- Appendix II T. Munatius Plancus Bursa -- Bibliography -- Index of People -- Index of Topics.